Identification of successful competitive combinations in the section of kickboxing pointfighting - Poteryakhin, A. A.; Kondakov, V. L.; Usatov, A. N.; Bocharova, V. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify effective competitive combinations in the point fighting kickboxing section, based on an assessment of the results of the performances of winners and prize-winners at major international competitions.